The changes of geodynamic stresses of the earth-crust in the Ignalina nuclear power plant region - Zakarevičius, Algimantas; Stanionis, Arminas (Geodesy and Cartography, 2012)
The study was performed with intent to apply the inverse Hook’ law – to describe connections between horizontal deformations of the Earth-crust and geodynamic stresses; tensor methods of stress estimation were based theoretically and experimental calculations were carried out in the territory of the Ignalina Nuclear Power Plant region. New data of the study of geodynamic stress change that are significantly related to a tectonic structure of the territory were obtained. Having analysed and generalised the results of calculation according to geodetic surveys, a tectonic activity in the surroundings of the graben Drūkšiai was established. The conclusion is drawn that the inverse Hook’ law, by describing the connections between horizontal movements of the Earth-crust and geodynamic stresses, may be used practically and applied for estimating the regularities of the geodynamic stress change.Article in Lithuanian.Geodinaminių žemės plutos įtampų pokyčiai Ignalinos atominės elektrinės regioneSantrauka. Tyrimas atliktas siekiant pritaikyti atvirkštinį Huko fizinį dėsnį horizontaliųjų Žemės plutos deformacijų bei geodinaminių įtampų sąsajoms aprašyti, teoriškai pagrįsta tenzorinė įtampų įvertinimo metodika bei atlikti eksperimentiniai žemės plutos įtampų Ignalinos atominės elektrinės regiono teritorijoje skaičiavimai. Gauti nauji geodinaminių įtampų pokyčių duomenys, kurie akivaizdžiai yra susiję su teritorijos tektonine sandara. Išanalizavus skaičiavimo pagal geodezinių matavimų duomenis rezultatus ir apibendrinus, nustatytas tektoninis aktyvumas Drūkšių grabeno aplinkoje. Daroma išvada, kad atvirkštinis Huko dėsnis, nusakant horizontaliųjų Žemės plutos judesių bei geodinaminių įtampų sąsajas, gali būti taikomas praktiškai bei įvertinant geodinaminių įtampų pokyčių dėsningumus.Raktažodžiai: GPS, geodinaminiai procesai, tektoninės įtampos, Žemės plutos deformacijos.First published online: 03 Aug 2012